Policing and Punishing Illegal Gun Behavior: An Examination of Jail Detainee Experiences with Gun Law Enforcement In Los Angeles. (20th July 2021) - Barragan, Melissa
Abstract: Drawing upon 140 interviews with individuals detained on gun-related charges, this article examines how participants' experiences with gun-related policing and punishment shaped their beliefs and behaviors surrounding guns and gun violence. Findings suggest that respondents characterized many of their gun-related experiences as unjust. They argue that their policing encounters reinforced discriminatory practices and stereotypes, undermining a key feature of procedural and distributive justice – impartiality. Respondents' experiences with police harassment and neglect attenuated their willingness to seek out and cooperate with the police by communicating that the law was not designed to serve marginalized groups, who often are treated as suspects first and victims second. By contrast, gang enhancements were key in shaping respondents' perceptions of unjust punishment, as these severe penalties also revealed inequities by race/ethnicity, class, and other social characteristics. The legitimacy erosion and sense of failed protection by the state produced by these encounters ultimately helped to create a context whereby illegal gun carry was positioned as a necessary strategy. Findings from this study extend existing scholarship on justice perceptions by demonstrating how specific policing, punishment, and criminalization processes can damage the law's legitimacy and inadvertently encourage the violence that the law was designed to deter.